A fast and compact algorithm for large-scale TSP optimization - Xu, Yihan (Nanyang Technological University, 2022)
This project proposes a fast and compact algorithms for solving large-scale TSP problems. It is based on three stages: Separation, Solution for small TSP, Fusion. The result shows that compared to the traditional heuristic algorithms, the new algorithm can reach a good balance between the time-cost and the quality of the solutions.